The relationship between the number of statutes coming into force and the number of regulations coming into force: Findings from empirical studies - Ciurak, Patryk (Ruch Prawniczy, Ekonomiczny i Socjologiczny, 2024)
The aim of this paper is to empirically test the opinion, common in legislative practice, that there is a relationship between the number of statutes and the number of regulations, and to measure the strength and nature of this relationship, if it exists. The data used in the study were obtained from the Polish legal database System Informacji Prawnej Lex and were analysed using Spearman’s correlation and negative binomial regression methods. The results confirmed the existence of the abovementioned relationship, which can be described as strong and exponential. An equation was also formulated to predict the number of regulations that will come into force based on the projected number of statutes coming into force in a given month. The results obtained provide an empirical addition to the extensive legal literature on the regulation as a normative act. They also highlight a possible path for the study of law, particularly in comparative law.